2021
DOI: 10.1136/openhrt-2021-001666
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ST segment elevation myocardial infarction hospitalisations in China from 2011 to 2015

Abstract: ObjectiveAccess to acute cardiovascular care has improved and health services capacity has increased over the past decades. We assessed national changes in (1) patient characteristics, (2) in-hospital management and (3) patient outcomes among patients presenting with ST segment elevation myocardial infarction (STEMI) in 2011–2015 in China.MethodsIn a nationally representative sample of hospitals in China, we created two random cohorts of patients in 2011 and 2015 separately. We weighted our findings to estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…ST‐segment elevation myocardial infarction (STEMI), defined as ST‐segment elevation in two anatomically contiguous leads, is the most urgent manifestation of coronary artery disease 1,2 . Over the past decade, the number of new STEMI cases is increasing in China annually, meanwhile, its mortality is constant 3 . Concerning the STEMI treatment, for patients with symptom onset within 12 h, percutaneous coronary intervention (PCI) is the preferred strategy to restore myocardial perfusion as soon as possible 4–6 .…”
Section: Introductionmentioning
confidence: 99%
“…ST‐segment elevation myocardial infarction (STEMI), defined as ST‐segment elevation in two anatomically contiguous leads, is the most urgent manifestation of coronary artery disease 1,2 . Over the past decade, the number of new STEMI cases is increasing in China annually, meanwhile, its mortality is constant 3 . Concerning the STEMI treatment, for patients with symptom onset within 12 h, percutaneous coronary intervention (PCI) is the preferred strategy to restore myocardial perfusion as soon as possible 4–6 .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we observed that the proportion was a little bit lower in China (11.8%), with the estimate comparable to that in the China PEACE-Retrospective Acute Myocardial Infarction Study (9.7%) [ 21 ]. Moreover, the China PEACE study even reported a significant decrease in the proportion of patients with no SMuRFs at the time of admission from 2011 to 2015 (11 to 5.5%) [ 16 , 21 ]. Nevertheless, considering the total number of STEMI patients almost nearly doubled in China at the same period [ 16 ], there was a substantial absolute number of patients presenting life-threatening STEMI without any SMuRF who cannot benefit from primary prevention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Our subgroup analysis stratified by hospital levels also supports this hypothesis that the adjusted association was less pronounced in province-level or prefecture-level hospitals compared with county-level hospitals although the interactive effect was not significant. Therefore, it is critical to improve the quality of the medical care system in these developing countries like China, especially for those remote areas with limited medical resources and low public awareness of ACS [ 15 , 16 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of women was much lower than that of men who were hospitalized for STEMI (28.1 vs 71.9%, P < 0.001), consistent with what had been reported in the literature. 17 However, once STEMI occurs, women usually have a higher risk of readmission than men, regardless of whether PCI was performed. 11 Our study also confirmed sex-based differences, with 2.4 times higher risk of readmission of female survivors than male survivors (OR = 2.426; 95% CI: 1.395–4.218; P = 0.002).…”
Section: Discussionmentioning
confidence: 99%